Analisis Pemendekan Gairaigo dalam Komik Detective Conan karya Gosho Aoyama chapter 1000-1040 - Bestia Dwi Putri; Damai Yani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2020)
Abstract The purpose of this research to determine the shortening process of gairaigo that found in Detective Conan comics by Gosho Aoyama chapter 1000-1040. The type of research is qualitative research with descriptive methods. The data used in this research is the absorption vocabulary (gairaigo) that contained in Detective Conan's comics by Gosho Aoyama chapter 1000-1040. The data source taken is shortening of gairaigo in the Detective Conan comic by Gosho Aoyama in chapter 1000-1040. Based on research results from 161 gairaigo data, there were 29 data are gairaigo whose word formation is derived from shortening wich dividen into 7 clipping data consists of 6 back-clipping and 1 fore-clipping, 20 compound truncation consists of 8 morpho-ortographic truncation compound clipping and 4 ellipsis, also 2 data is combination of clipping and ellipsis.Keywords: shortening, gairaigo.